Wage and occupational assimilation by skill level: Migration policy lessons from Spain - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2012)
What are the migration policy lessons that can be learned from the Spanish case? Unlike countries with a large tradition of receiving immigrants, in Spain having a high-school degree does not give immigrants an advantage in terms of wage or occupational assimilation (relative to their native counterparts). This paper discusses the potential explanations behind this result and analyzes the consequences of this result in terms of migration policy recommendations.
Keywords: J15; J24; J61; J62; 330; wage assimilation; occupational assimilation; education; migration policy; Wirtschaftskrise; Arbeitsmarkt; Arbeitslosigkeit; Arbeitsmarktreform; Erwerbstätigkeit; Arbeitsangebot; Alternde Bevölkerung; Fachkräfte; Deutschland